Effectiveness of perindopril/amlodipine fixed-dose combination in the treatment of hypertension: a systematic review - Dat, Truong Van; Tu, Vo Linh; Thu, Le Nguyen Anh; Quang, Nguyen Nhat Anh; Binh, Van; Nga, Nguyen Thi Quynh; Loc, Duong Hoang; Nguyen, Tran Thi Hong; Tam, Dao Ngoc Hien; Huynh, Hong-Han; Trung, Tran Dinh; Do, Uyen; et al. (Frontiers in Pharmacology, 2024)
Background: Uncontrolled blood pressure is a major risk factor for cardiovascular diseases. Fixed-dose combination (FDC) therapy offers a promising approach to address this challenge by providing a convenient single-tablet solution that enhances the effectiveness of blood pressure control. In our systematic review, we assess the effectiveness of the FDC perindopril/amlodipine in managing blood pressure. Methods: We conducted a comprehensive search across four primary electronic databases, namely PubMed, Virtual Health Library (VHL), Global Health Library (GHL), and Google Scholar, as of February 8th, 2022. Additionally, we performed a manual search to find relevant articles. The quality of the selected articles was evaluated using the Study Quality Assessment Tools (SQAT) checklist from the National Institute of Health and the ROB2 tool from Cochrane. Results: Our systematic review included 17 eligible articles. The findings show that the use of perindopril/amlodipine FDC significantly lowers blood pressure and enhances the quality of blood pressure control. Compared to the comparison group, the perindopril/amlodipine combination tablet resulted in a higher rate of blood pressure response and normalization. Importantly, FDC perindopril/amlodipine contributes to improved patient adherence with minimal side effects. However, studies conducted to date have not provided assessments of the cost-effectiveness of FDC perindopril/amlodipine. Conclusion: In summary, our analysis confirms the effectiveness of FDC perindopril/amlodipine in lowering blood pressure, with the combination therapy outperforming monotherapy and placebo. While mild adverse reactions were observed in a small subset of participants, cost-effectiveness assessments for this treatment remain lacking in the literature.